The Role of Education in Reducing Stigma of Mental Health Problems in Schools and Increasing Support for Students - Kurniawan, Yulius; Seran, Gregorius (Bulletin of Science, Technology and Society, 2024)
Stigma surrounding mental health issues in educational settings remains a significant barrier for students in accessing support and managing their emotional well-being. This study aims to investigate the role of education in reducing mental health stigma and fostering a more inclusive and empathetic school environment. Using a literature review approach, the article synthesizes findings from various academic sources to highlight the importance of accurate, culturally sensitive, and age-appropriate mental health education. It emphasizes the need for comprehensive teacher and staff training to identify early symptoms of psychological distress and respond with empathy and without discrimination. Furthermore, the availability of accessible and confidential counselling services within schools is identified as a key factor in building a supportive climate. The study also underscores the importance of collaboration between schools, families, and communities in promoting mental health literacy and creating a safe space for students to thrive. By addressing stigma through education and systemic support, schools can play a transformative role in safeguarding students’ mental health and promoting long-term psychological resilience.